2017
DOI: 10.1037/lhb0000229
|View full text |Cite
|
Sign up to set email alerts
|

Is the effect of justice system attitudes on recidivism stable after youths’ first arrest? Race and legal socialization among first-time youth offenders.

Abstract: Youth who hold negative attitudes toward the justice system are more likely to engage in crime. It is particularly important to study attitudes early in someone's criminal career when they may still be open to change. To date, however, there has been no empirical test assessing whether the relation between attitudes and behavior changes after a first arrest. Using a sample of 1,216 first-time, male, juvenile offenders from the Crossroads Study, the present study explored: (a) racial/ethnic differences in the l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
44
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 42 publications
(48 citation statements)
references
References 84 publications
4
44
0
Order By: Relevance
“…This finding warrants special concern because, in our sample, prior law-abiding behaviors did not protect boys against future police stops, yet being stopped by police was associated with increased engagement in delinquent behavior. Our findings are consistent with previous research that found nondelinquent black and Latino boys faced the same risk of police surveillance as self-reported delinquent boys (23, 38, 40, 42, 45, 76) and that these experiences were likely to induce criminal behavior (22, 25, 44, 77). Because adolescent girls of all races and adolescent white boys and girls are less likely to report police-initiated contact than boys and nonwhite youth, future research should explore whether the relationships tested in the present study extend to these populations that are less frequently stopped by police.…”
Section: Discussionsupporting
confidence: 92%
“…This finding warrants special concern because, in our sample, prior law-abiding behaviors did not protect boys against future police stops, yet being stopped by police was associated with increased engagement in delinquent behavior. Our findings are consistent with previous research that found nondelinquent black and Latino boys faced the same risk of police surveillance as self-reported delinquent boys (23, 38, 40, 42, 45, 76) and that these experiences were likely to induce criminal behavior (22, 25, 44, 77). Because adolescent girls of all races and adolescent white boys and girls are less likely to report police-initiated contact than boys and nonwhite youth, future research should explore whether the relationships tested in the present study extend to these populations that are less frequently stopped by police.…”
Section: Discussionsupporting
confidence: 92%
“…More generally, studies that take a static approach have linked cumulative police-initiated encounters to lower ratings of legitimacy and effectiveness, supporting the idea that "in each instance, respondents with more experience were more inclined to see each additional stop as unjustified, legally questionable, and characterized by unfair and poor treatment" and, as such, "increasingly unreasonable and antagonizing" (Tyler et al 2014:771; also Fratello, Rengifo, and Trone 2013; but see Fine et al 2017;Viki et al 2006). Leiber, Nalla, and Farnworth (1998) report similar results from surveys of young adjudicated males, which show that views of police fairness are lower for persons with more frequent police warnings or police bookings (see also Murphy and Cherney 2011).…”
Section: How Does Contact Matter For Reporting Intentions?mentioning
confidence: 93%
“…However, these studies do not focus on the link between perceived quality of police behavior during contact and changes in attitudes towards the police. Some studies focused on changes in legal attitudes over time and did not include information regarding police-citizen encounters(Kaiser and Reisig 2019;Piquero et al, 2005;Schubert et al, 2016), whereas others investigated the legal socialization process while taking into account previous arrests(Augustyn, 2016;Fine et al, 2016;Fine et al, 2017) and whether respondents had been picked up by the police(Fine and Cauffman, 2015;McLean et al, 2018) -but none of them engaged in comparisons of expected changes in attitudes between respondents who satisfactory, unsatisfactory, and no police contact.…”
mentioning
confidence: 99%